PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ULAR TANGGA TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Oktavia Erlina, Riri; Dayu R. Perdana; Hariyanto; Fadhilah Khairani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is the low learning outcomes of Pancasila Education for fourth-grade students at SD Negeri five Bandar Jaya. The purpose of this study is to determine the significant effect of the snake and ladder learning media on the learning outcomes of Pancasila Education for students and the significant difference in the average learning outcomes of Pancasila Education between the snake and ladder learning media and the Student Worksheet (LKPD) learning media. The research method used was a quasi-experiment. The research design used was a non-equivalent control group design. The research population consisted of five-two participants, and the sample consisted of five-two students, which was determined using total sampling technique. Data collection techniques included tests and non-tests. The hypothesis tests used were simple linear regression and independent sample t-tests. The results obtained from the first hypothesis test, Fcount>Ftable, indicate that there is a significant effect of the snake and ladder learning media on the Pancasila Education learning outcomes of fourth-grade students at SD Negeri five Bandar Jaya in the 2025/2026 academic year. and the second hypothesis, thitung>ttabel, means that there is a significant difference in the average Pancasila Education scores between the experimental group (using the snake and ladder learning media) and the control group (using the LKPD learning media) of fourth-grade students at SD Negeri five Bandar Jaya in the 2025/2026 academic year.